1993
DOI: 10.1128/jvi.67.4.2276-2284.1993
|View full text |Cite
|
Sign up to set email alerts
|

Human HLA class I- and HLA class II-restricted cloned cytotoxic T lymphocytes identify a cluster of epitopes on the measles virus fusion protein

Abstract: The transmembrane fusion (F) glycoprotein of measles virus is an important target antigen of human HLA class I- and class II-restricted cytotoxic T lymphocytes (CTL). Genetically engineered F proteins and nested sets of synthetic peptides spanning the F protein were used to determine sequences of F recognized by a number of F-specific CTL clones. Combined N- and C-terminal deletions of the respective peptides revealed that human HLA class I and HLA class II-restricted CTL efficiently recognize nonapeptides or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…RSV infected cells were used as antigen presenting cells when at least 30% of the cells were found positive. Before use in T cell stimulation experiments RSV infected and control B-LCL were UV irradiated essentially as described previously for measles infected B-LCL (302 nm, 2.5 × 10 −2 W/mm 2 ) [Van Binnendijk et al, 1993].…”
Section: Establishment and Rsv Infection Of B-lclmentioning
confidence: 99%
“…RSV infected cells were used as antigen presenting cells when at least 30% of the cells were found positive. Before use in T cell stimulation experiments RSV infected and control B-LCL were UV irradiated essentially as described previously for measles infected B-LCL (302 nm, 2.5 × 10 −2 W/mm 2 ) [Van Binnendijk et al, 1993].…”
Section: Establishment and Rsv Infection Of B-lclmentioning
confidence: 99%
“…suggested as responsible for the induction of memory T cells that produce Th2-like rather than Th1-like cytokines (6,32,40). Class II-restricted CTL responses have been noted for a number of other RNA viruses, including parainfluenza and Sendai viruses (4,10,14), measles viruses (38,39), and coronavirus (19) in the family Paramyxoviridae and recently for influenza virus (13,34) in the family Orthomyxoviridae. Limiting dilution analysis of parainfluenza virus-specific CD4 ϩ and CD8 ϩ T lymphocytes from the peripheral blood of adults showed relatively high frequencies for both CD4 ϩ (1:4,700) and CD8 ϩ (1:2,500) CTLps (10).…”
Section: Discussionmentioning
confidence: 99%
“…Limiting dilution analysis of parainfluenza virus-specific CD4 ϩ and CD8 ϩ T lymphocytes from the peripheral blood of adults showed relatively high frequencies for both CD4 ϩ (1:4,700) and CD8 ϩ (1:2,500) CTLps (10). Measles virus infection in humans has been shown to induce both HLA class I-and class II-restricted CTLs specific to the transmembrane fusion glycoprotein (39). In mice, Sendai virus-specific class II-restricted T-cell responses have been investigated and defined (4,13).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the cell-mediated component is therefore clear, in particular the CD8+ lymphocyte response. Studies on primates have shown that even the peak of viremia and its duration were independent of B-lymphocyte deficiency if it was associated with that of the CD8+ component [59].…”
Section: Measles and Immunitymentioning
confidence: 99%